The Effect of Discipline, Work Motivation, Work Expenses on Employee Performance Through Work Satisfaction - Catharina Theo; Idayanti Nursyamsi; Musran Munizu (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
The ability of human resources is a significant determinant of organizational performance and competitive advantage, HR is a determining factor for organizational success obtained from employee performance. This study aims to determine and analyze the effect of work discipline, work motivation, and workload on employee performance through job satisfaction. This research was conducted at the General and Equipment Section, Hasanuddin University. The research method used is the descriptive survey method with primary data collection in the form of questionnaires to the respondents. The research sample was 109 respondents. The data analysis technique used descriptive statistical analysis and path analysis. The results of the study found that work discipline and work motivation had a positive and significant effect on job satisfaction and employee performance, the workload variable had a negative and significant effect on employee satisfaction and performance. Furthermore, job satisfaction has a positive and significant effect on employee performance. The results of mediation testing show that job satisfaction can partially mediate the effect of work discipline, work motivation, and workload on employee performance.